Crop Establishment Methods and Weed Management Practices Affects Crop Growth, Yield, Nutrients Uptake and Weed Dynamics in Wheat - Singh, Ravi Prakash; Verma, S. K.; Kumar, Sushil (International Journal of Bio-resource and Stress Management, 2017)
The field experiment was conducted during winter (rabi) of 2014 and 2015 at Agricultural Research Farm, Institute of Agricultural Sciences, BHU, Varanasi. The experiment was conducted with twenty four treatment combinations consisting of four crop establishment methods in wheat viz., conventional tillage (CT) no-residue, CT with residue, zero tillage (ZT) no residue, ZT with residue as main plots and six weed management practices viz., weedy check, weed free, mesosulfuron {12 g a.i. ha-1 at 30 days after sowing (DAS)} followed by (fb) one hand weeding at 45 DAS, metsulfuron (4 g a.i. ha-1 at 30 DAS) fb one hand weeding at 45 DAS, clodinafop+metsulfuron (60+4 g a.i. ha-1 at 30 DAS) and mesosulfuron+iodosulfuron (12+2.4 g a.i. ha-1 at 30 DAS) as sub plots in split-plot design with three replications, to evaluate the influence of crop establishment methods and weed management practices on crop growth, yield, nutrients uptake and weed dynamics. Results showed that ZT with residue recorded the lowest weeds density and dry weight, nutrients depletion by weeds and the highest weed control efficiency (WCE). However, CT with residue adjudged superior with respect to crop growth parameters, yield, and nutrients uptake by crop. Among herbicidal treatments, mix application of mesosulfuron+iodosulfuron recorded significantly lowest weeds density and dry weight and nutrients depletion by weeds and also recorded maximum WCE, plant height, number of tillers, crop dry weight, leaf area index (LAI), chlorophyll content, yield, and nutrients uptake over rest of the herbicidal treatments. The interaction between crop establishment methods and weed management practices was found to be significant only for grain and straw yield.